2009
DOI: 10.1007/s10811-009-9415-z
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous effect of irradiance and temperature on biochemical composition of the microalga Pavlova lutheri

Abstract: The biochemical composition of microalgae can be modulated through the environmental conditions prevailing during growth. The simultaneous effects of irradiance and temperature on the biochemical composition of Pavlova lutheri were evaluated using an experimental star factorial design. Five levels were tested for each parameter (temperature, 10, 14, 18, 22 and 26°C; irradiance, 60, 105, 150, 195 and 240 μmol photons m −2 s −1 ), whereas the carbohydrate, protein, lipid, pigments and elementary compound conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
38
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(48 citation statements)
references
References 30 publications
7
38
0
3
Order By: Relevance
“…The biochemical compositions of algae (such as protein, carbohydrate, lipid, amino acid and pigments composition) change with respect to temperature, light, nutrient media components, strain characteristics and growth phase. The microalgae can grow under different temperatures and the temperature affects the structure of cell compounds, the chemical reactions, enzymatic activity, membrane liquidity, the efficiency of electron transfer chain and other metabolic mechanisms [28]. The temperature in culture media in the present study was determined to be between 22-25 °C and C. vulgaris cultures showed good development under that temperature.…”
Section: Resultsmentioning
confidence: 72%
“…The biochemical compositions of algae (such as protein, carbohydrate, lipid, amino acid and pigments composition) change with respect to temperature, light, nutrient media components, strain characteristics and growth phase. The microalgae can grow under different temperatures and the temperature affects the structure of cell compounds, the chemical reactions, enzymatic activity, membrane liquidity, the efficiency of electron transfer chain and other metabolic mechanisms [28]. The temperature in culture media in the present study was determined to be between 22-25 °C and C. vulgaris cultures showed good development under that temperature.…”
Section: Resultsmentioning
confidence: 72%
“…In contrast, Carvalho et al (2009) reported absence of strong relation between light intensity and carbohydrate or starch accumulation, suggesting either carbon limitation or elimination of other carbon sinks such as protein synthesis or cell division.…”
Section: Light Intensitymentioning
confidence: 84%
“…La disminución en el contenido de clorofila a como consecuencia del incremento en el nivel de irradiancia sobre cultivos microalgales se ha descrito previamente (Miskiewicz et al 2002, Carvalho et al 2009), esto coincide con los resultados evidenciados en esta investigación. Masuda et al (2003) indicaron que bajas irradiancias, inducen en las células el incremento de pigmentos fotosintéticos tales como clorofila a a fin de aumentar su capacidad para captación de luz (Mock & Kroon 2002) y optimizar la eficiencia del fotosistema dos (PSII) (Janknegt et al 2008).…”
Section: Resultsunclassified